2019
DOI: 10.3390/fib7090075
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Arundo donax Fibers for Oil Spill Recovery Applications

Abstract: In the last years, natural fibers are increasingly investigated as an oil recovery system in order to overcome the oil spillage phenomena, thus preserving environment and aquatic life. In particular, lignocellulose-based fibers have recently been employed with promising results. In such a context, the aim of this paper is to assess the oil sorption capability of natural fibers extracted from the stem of the giant reed Arundo donax L., a perennial rhizomatous grass belonging to the Poaceae family that grows nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In this context, the low selectivity of the pollutants from the water necessitates a secondary separation process, which increases the costs and times of removing the oil spilled from the water's surface 7 . Conventional oil sorbents (e.g., synthetic, mineral, and vegetable materials) are characterized by a low oil/water selectivity and low oil‐sorption capacity 8–10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the low selectivity of the pollutants from the water necessitates a secondary separation process, which increases the costs and times of removing the oil spilled from the water's surface 7 . Conventional oil sorbents (e.g., synthetic, mineral, and vegetable materials) are characterized by a low oil/water selectivity and low oil‐sorption capacity 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…7 Conventional oil sorbents (e.g., synthetic, mineral, and vegetable materials) are characterized by a low oil/water selectivity and low oil-sorption capacity. [8][9][10] Recently, due to their macroporous structure, flexibility, and low cost, porous materials such as foams have been identified as promising candidates for spill oil clean-up. 6 In addition, the foams show suitable mechanical properties in terms of elasticity and deformability.…”
mentioning
confidence: 99%
“…The ADL fiber morphology is made up of an irregular tube size. Like major natural fibers, the ADL fibers’ surface morphology is formed of several elementary fibers that are joined together throughout their length by pectin and other noncellulosic substances . Likewise, the fiber surface clearly shows some impurities.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, 300-2500 μm long fibers showed porous orthotropic morphology but distinct adsorption capacity to different pollutant viscosity. The result showed that the smaller these fibers were, the better oil uptake in high viscosity liquid that contained one kind of oil, such as kerosene, pump oil, virgin naphtha, and crude oil (Fiore et al 2019). The milkweed (Asclepias syriaca) floss had a superhydrophobic trait and hollow structure occupying 90% of its total volume.…”
Section: Removal Of Oils By Invasive Plantsmentioning
confidence: 99%